2019
DOI: 10.1038/s41467-019-13367-z
|View full text |Cite
|
Sign up to set email alerts
|

Orbitally dominated Rashba-Edelstein effect in noncentrosymmetric antiferromagnets

Abstract: Efficient manipulation of magnetic order with electric current pulses is desirable for achieving fast spintronic devices. The Rashba-Edelstein effect, wherein a spin polarization is electrically induced in noncentrosymmetric systems, provides a mean to achieve current-induced staggered spin-orbit torques. Initially predicted for spin, the orbital counterpart of this effect has been disregarded up to now. Here, we present a generalized Rashba-Edelstein effect, which generates not only spin polarization but also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…It is well known that the Rashba state originates in a chiral orbital angular momentum texture [44][45][46]. Such an orbital Rashba effect persists even in the absence of spin-orbit coupling, which induces current-induced orbital dynamics and transport [47,48]. Through spin-orbit coupling, the orbital Rashba state couples to the spin and the spin texture emerges, thus leading to spin dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the Rashba state originates in a chiral orbital angular momentum texture [44][45][46]. Such an orbital Rashba effect persists even in the absence of spin-orbit coupling, which induces current-induced orbital dynamics and transport [47,48]. Through spin-orbit coupling, the orbital Rashba state couples to the spin and the spin texture emerges, thus leading to spin dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The generated spin current can be transmitted into the adjacent FM layer, and the resulting torque can switch the magnetization of FM layer. [ 5,6,16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…The generated spin current can be transmitted into the adjacent FM layer, and the resulting torque can switch the magnetization of FM layer. [5,6,[16][17][18] magnetism, [33] and also which has the high magnetic moment of 8 μ B and it has a very capable for changing the properties of the material. [34] Furthermore, Gd posses very stable intermetallic phases such as PtGd, [35] which would have strong SHE that can be utilized as a spin current source to generate highly efficient SOT.…”
Section: Introductionmentioning
confidence: 99%
“…LEE was first theoretically proposed [8] and then experimentally realized [9,10]. Recently, there has been growing interest in LEE [5,[11][12][13], and it was suggested that LEE can potentially switch the magnetic orderings of magnetic materials [5,13]. However, LEE only exists in metallic systems, and the electric field also generates a charge current (Ohm current).…”
Section: Introductionmentioning
confidence: 99%